Pemanfaatan Limbah Penyamakan Kulit Menjadi Gelatin untuk Industri Pangan - Sugihar tono (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Solid wastes generated from tanning process create a major problem for leather industry, if not handled properly will cause problem and invironmental pollution.The tanning process of 1000 kg raw hide, will yield 150-200 kg leather and generated nearly 850 kg as solid wastes, that is consist of solid wastes generated during pre-tanning processes as much as 80 %, while 20 % of of the wastes are caused by post tanning processes. Waste that can be processed into gelatin for food industry are generated during pre-tanning process. Acid process produce type A gelatin, with higher yield than the alkaline process. Alkaline process produces B gelatin with gelatin characteristics such as molecular weight, viscosity, and gel strength is better than the acid process. Gelatin for food industry use : foam-forming, binders, stabilizers, fillers, coatings, nutrien enrichment, precipitate, gelling, adhesive, viscosity enhancers, emulsifier, finning agent, crystal modifier, and tickeners.